2019
DOI: 10.1007/s11883-019-0770-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Cardiovascular Disease: Insights and Challenges for Considering Food Groups and Nutrient Sources

Abstract: Purpose of Review The relationship between dietary patterns and cardiovascular disease has been the subject of much research, but an important methodological consideration is the interdependence between the nutrient composition of foods and the recognition of healthy dietary patterns. This review considers some of the challenges in researching dietary patterns with implications for translation to public health promotions. Recent Findings A number of statistical methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Nutrition plays an increasingly important role in the prevention of chronic diseases including CHD and type 2 diabetes mellitus (T2DM) (1,2) . The global prevalence of T2DM is increasing.…”
mentioning
confidence: 99%
“…Nutrition plays an increasingly important role in the prevention of chronic diseases including CHD and type 2 diabetes mellitus (T2DM) (1,2) . The global prevalence of T2DM is increasing.…”
mentioning
confidence: 99%
“…Dietary fibre is one of the components of food that has a significant impact on health, and since the 1980s research results on the anticancer effects of fibre have been published [23,62,63,64]. As a result of the research, Howe et al found that an increase in fibre intake by 13 g/day reduces the risk of cancer by 31% [65,66].…”
Section: Resultsmentioning
confidence: 99%
“…Cardiovascular diseases, including coronary artery diseases, stroke, heart failure, and hypertension, are the first cause of death in Western countries. A large number of naturally occurring compounds and foods are promoted for the prevention of such diseases (Allawadhi, Khurana, Sayed, Kumari, & Godugu, ; Tapsell, Neale, & Probst, ). Accordingly, a number of observational and intervention studies has explored the possible association between the intake of polyphenol‐rich foods (e.g., beverages such as cocoa, fruit and vegetables, tea, extra virgin/virgin olive oil, and wine) and cardiovascular diseases.…”
Section: Polyphenol Intake and Human Healthmentioning
confidence: 99%